Epidemiology Study for Cancer Incidences among Patients from Baghdad Carrying Different Types of Cancer - Ali, Hassan Nafal (Iraqi Journal of Cancer and Medical Genetics, 2017)
This study was carried out in Al-Yarmook hospital, laboratories department, Baghdad- Iraq; One hundred thirty three Iraqipatients have been recorded during period May 2014 until December 2014. The current study has demonstrated that fivedifferent types of the following cancers: Breast cancer, Skin cancer, colorectal cancer, Bladder cancer and endometrial cancerwere enrolled in this study. Comparison among each type of cancer was regarded in age, sex and number. The majority resultsin cancer epidemiology for the present study were fluctuated between the skin and breast cancer, which showed 33.1% andthis, represented the prevalence of cancer among all the other types of cancers. In case of other types, the result has showed16.5 %, 13.5% and 3.7 % for endometrial cancer, Bladder cancer and colorectal cancer, respectively.Keywords: Types of Cancer, Epidemiology Study.